Nanocompósitos à base de MG: processamento, estrutura e propriedades de novos materiais para armazenagem de hidrogênio - Leiva, Daniel Rodrigo (Universidade Federal de São Carlos, 2006)
Magnesium is light, abundant and it can store up to 7.6 wt. % of hydrogen forming the hydride MgH2 and therefore it is a promising material for hydrogen storage. However, the H-sorption occurs at relatively high temperatures with slow kinetics. Beside this, Mg and MgH2 surfaces are highly reactive, easily forming oxide or hydroxide layers that lower the level of storage properties. Mg-based nanocomposites have been studied in the last few years to overcome these limitations. The grain size reduction of Mg or MgH2 to the nanometric scale and the addition of catalysts as transition metals or its hydrides can promote fast kinetics at lower temperatures. The formation of a fluorinated layer on Mg surface enhances its stability in the sorption cycles avoiding the usual contamination with oxygen. Reactive milling under H2 atmosphere is one of the processing routes that has been recently investigated for the preparation of Mg-based nanocomposites, and promising results have been obtained. In the present work, the effects of different nanocrystalline additives (MgF2, Fe, NbH0,89, FeF3, VF3) into Mg processed by reactive milling were studied. The aspects analysed in this work were the influence of the additives in MgH2 synthesis during milling and in the desorption behavior. A combined catalytic effect was observed due to the MgF2 and Fe (or NbH0,89) action in MgH2 synthesis during processing. The transition metal fluorides also promote MgH2 synthesis. A fluorine transfer reaction occurs from the fluoride to Mg, generating MgF2 and transition metal (or its hydride) nanoparticles in the mixture. An important catalytic effect of Fe during H-desorption of MgH2 was also observed.
Mg-based nanocomposites: processing, structure and properties of new hydrogen storage materials
Keywords: Metalurgia; Armazenagem de hidrogênio; Nanocompósitos; Catalisadores; Hidretos de magnésio; Moagem de alta energia; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA